Enhancing the Photovoltaic Performance of Nonfullerene Acceptors via Conjugated Rotatable End Groups. Issue 31 (20th September 2018) - Yu, Runnan; Yao, Huifeng; Hong, Ling; Xu, Ye; Gao, Bowei; Zhu, Jie; Zu, Yunfei; Hou, Jianhui
Abstract: Unlike varieties of well‐known nonfullerene acceptors with rigid chemical structures, an acceptor–donor–acceptor (A–D–A)‐type acceptor with conjugated rotatable end groups, a phenylethynyl‐substituted acceptor (ITPN) is designed and synthesized. Compared with the ethynyl‐substituted acceptor (ITEN) and a well‐know small molecular electron acceptor (ITIC), ITPN molecules show reduced binding energy and reorganization energy, facilitated by the rotatability and the extended π conjugation of phenylethynyl end groups. ITPN shows stronger molecular aggregation and more ordered arrangement, resulting in enhanced charge‐transport properties. In the polymer solar cells, applying the fluorinated polymer (PBDB‐TF) as the electron donor, the device based on ITPN yields a maximum power conversion efficiency of 12.6%, higher than that of an ITEN‐ or ITIC‐based device. The work demonstrates that chemically modulating the end groups by the synergistic effect of rotatable end groups and extending the π‐conjugation length is an effective and straightforward way to improve the photovoltaic performance of A–D–A‐type small molecular acceptors. Abstract : Non‐fullerene acceptors with rotatable end‐groups (ITEN and ITPN) are synthesized by introducing ethynyl or phenylethynyl substituents to modify the well‐known acceptor (ITIC). The ITPN‐based device shows enhanced charge transport capacities and demonstrates a PCE of 12.6%, demonstrating the synergistic effect of rotatable end‐groups and extending the π‐conjugated length is effective to enhance the photovoltaic performances of A–D–A acceptors.